PROFIL KEMAMPUAN KOGNITIF MAHASISWA TADRIS IPA IAIN PALU PADA MATA KULIAH KONSEP DASAR IPA - Arda Arda (Program Studi Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Institut Agama Islam Negeri (IAIN) Palu, 2020)
This research is descriptive research. It aims to find out profile of cognitive abilities students of Tadris IPA IAIN Palu who programmed the Basic Concepts of Natural Sciences courses. The research instrument was multiple choice questions that refers to the six revised Bloom’s Taxonomy level. The results of data analysis showed that the percentage of cognitive abilities students of Tadris IPA category very high were 5.6%, high were 72.2%, medium were 16.7% and low were 5.6%. Students of Tadris IPA have the ability remembering (C1) were 86%, understanding (C2) were 72%, applying (C3) were 61%, analyzing (C4) were 77%, evaluating (C5) were 42% and creating (C6) were 6%. Students of Tadris IPA have Lower Order Thinking Skills (LOTS) higher than Higher Order Thinking Skills (HOTS). Therefore, learning needs to be done that can improve the ability of HOTS students of Tadris IPA.